2021
DOI: 10.3390/ijerph18137150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differential Perceptions and Barriers to Advance Care Planning in Dementia among Asian Patient–Caregiver Dyads—A Mixed-Methods Study

Abstract: A parallel mixed-methods study on 20 patient–caregiver dyads in an Asian population was conducted to explore the differential perceptions and barriers to ACP in dementia. We recruited English-speaking patients with mild dementia and their caregivers. A trained ACP facilitator conducted ACP counseling. Patient–caregiver dyads completed pre–post surveys and participated in post-counseling qualitative interviews. We used mixed-methods analysis to corroborate the quantitative and qualitative data. Differential per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…Conversely, there was also concerns by some patients that in doing their ACP, they would be showing mistrust in their FCGs to make the right EOL decisions for them. These findings are in concordance with findings by Ali et al 24 on English speaking Singaporean patients with mild dementia which found a similar pattern of transference of decision making to family members, leaving them to discuss with healthcare teams regarding treatment decisions. In the face of such deferment of decision making to the FCGs, FCGs ironically may be driven by feelings of guilt and filial piety to engage in life-extending treatments for patients at EOL.…”
Section: Planning For Cognitive Decline and Deathsupporting
confidence: 92%
“…Conversely, there was also concerns by some patients that in doing their ACP, they would be showing mistrust in their FCGs to make the right EOL decisions for them. These findings are in concordance with findings by Ali et al 24 on English speaking Singaporean patients with mild dementia which found a similar pattern of transference of decision making to family members, leaving them to discuss with healthcare teams regarding treatment decisions. In the face of such deferment of decision making to the FCGs, FCGs ironically may be driven by feelings of guilt and filial piety to engage in life-extending treatments for patients at EOL.…”
Section: Planning For Cognitive Decline and Deathsupporting
confidence: 92%
“…Barriers exist that must be overcome. For example, newly diagnosed early-stage dementia patients in Singapore were much less likely to acknowledge barriers to advance care planning than caregivers (10.5% versus 58%) [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 ) Similarly, a recent study suggested that socio-cultural factors pose barriers in initiating discussions about advance care planning in older persons with dementia. 14 ) Specifically, in Chinese culture, discussing matters related to death has been considered taboo. 15 ) In addition, it is not uncommon in Asian cultures for older people to leave end-of-life decisions to their family members.…”
Section: International and Regional Perspectivesmentioning
confidence: 99%